2019
DOI: 10.1093/jmcb/mjy087
|View full text |Cite
|
Sign up to set email alerts
|

The role of p53 in developmental syndromes

Abstract: While it is well appreciated that loss of the p53 tumor suppressor protein promotes cancer, growing evidence indicates that increased p53 activity underlies the developmental defects in a wide range of genetic syndromes. The inherited or de novo mutations that cause these syndromes affect diverse cellular processes, such as ribosome biogenesis, DNA repair, and centriole duplication, and analysis of human patient samples and mouse models demonstrates that disrupting these cellular process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 125 publications
(175 reference statements)
4
66
0
1
Order By: Relevance
“…Additional analysis of individual genes revealed that p53 signaling is increased in the XLID cells. These findings support the hypothesis that p53 activation might be a unique link between different genetic developmental disorders (13). Having established that the common feature of HUWE1-related XLIDs is deregulation of p53 pathway, we next focused on JMS, one of the most severe forms of XLID.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Additional analysis of individual genes revealed that p53 signaling is increased in the XLID cells. These findings support the hypothesis that p53 activation might be a unique link between different genetic developmental disorders (13). Having established that the common feature of HUWE1-related XLIDs is deregulation of p53 pathway, we next focused on JMS, one of the most severe forms of XLID.…”
Section: Discussionsupporting
confidence: 73%
“…Only very few of the JMS organoids that did develop had decreased size, which is in line with the microcephaly observed in JMS patients (4), and were characterized by reduced cellularity and lack of the laminar patterning, features reported previously in the mouse Huwe1 mouse models (9,10). Interestingly, the observation that elevated p53 activity accompanies neurodevelopmental impairments in JMS is supported by 11 recent studies showing that patients with germline TP53 mutations present with microcephaly (27), as well as that microcephaly and neurodevelopmental defects in several human neurodevelopmental disorders are p53-dependent (13). This supports the idea that deregulation of p53 activity could have central role in the onset of various neurological conditions.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These mice exhibit radiosensitivity, decreased in-vitro transformation potential, and reduced in vivo tumorigenesis 9,10 . Several studies also revealed a role for p53 overexpression in developmental disorders 11,12 . For example, the ribosomopathy model with reduced expression of ribosomal protein Rpl27a, displays endogenously elevated p53 and phenocopies mouse models of high p53 13 .…”
Section: Mainmentioning
confidence: 98%
“…The many biological functions and cellular processes regulated by p53 are also reflected by developmental syndromes that result from inappropriate p53 hyperactivation during embryogenesis, triggering apoptosis or restraining proliferation of certain cell types 5 . For other p53-controlled processes, like EMT and cellular differentiation, the etiology of these syndromes is currently unknown 5,6 . Many of these so-called p53-associated syndromes have been modeled in mice via introduction of mutations that affect various cellular processes converging on p53 activation.…”
Section: Introductionmentioning
confidence: 99%